Solo Broadcast Journalism in Industrial Revolution 4.0: Constructing of Solo Broadcast Journalism Model from Industrial Perspective - Aripin, Norizah; Ismail, Awan (UUM, 2021)
Social network is a rapidly growing source of news in broadcast journalism. Broadcast journalism is facing continuing decline in electronic media circulation and social media changes. The concept of online convergence broadcast journalism has become a news trend in social media. Solo broadcast journalism and social media are becoming a practice in news organizations today. Therefore, this article aims to identify the elements of solo broadcast journalism from an industry practitioner’s perspective. This study uses media accountability theory. A qualitative methodological approach was used in this study. Face-to-face interviews were conducted involving eight informants who practiced solo broadcast journalism. Data were analyzed thematically. The results showed that practices (production task, preparation task, etc.), importance of knowledge, skills and profession (use of technology, multi-tasking, work performance, etc.) ethics (honesty, credibility, etc.) and guidelines (producing news, producing photos, etc.) are among the elements of solo broadcast journalism in news organizations. The findings of this study are expected to benefit the National ICT Agenda on National Broadband Policy from the perspective of newspaper organizations in expanding the use of technology in the distribution and publication of stories for news. The findings of this study will help the appropriate adjustments to develop human capital that integrating practices broadcast journalist with technology-assisted work for solo broadcast journalism. In addition, this study is also significant to the National Education Policy. The study will impact the educational curriculum of broadcast journalism, by introducing changes which are in line with the development of solo broadcast journalism.